Typifications in the genus Cicendia Adans. (Gentianaceae) - Çiçek, Mehmet (Phytotaxa, 2014)
Nomenclatural types are confirmed for the majority of names associated with Cicendia Adanson (Gentianaceae); and a lectotype is here designated for Cicendia stricta.